Profile of Maytenus aquifolium action over free radicals and reactive oxygen species - Vellosa, José Carlos Rebuglio [UNESP]; Barbosa, Vanessa de Frias [UNESP]; Khalil, Najeh Maissar [UNESP]; De Aparecida Freitas Formenton Dos Santos Macedo, Vânia [UNESP]; Furlan, Maysa [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Mascarenhas de Faria Oliveira, Olga Maria [UNESP] (FapUNIFESP (SciELO), 2007)
Reactive oxygen species (ROS) and free radical species have been implicated in initiating, accompanying or causing many diseases in living organisms; there is thus, a continual need for antioxidants molecules to inactivate ROS/free radicals. Many studies of plants crude extracts have demonstrated free-radical scavenging and antioxidant action. Maytenus species have long been used, in several countries, as traditional medicines against gastric ulcers, dyspepsia and others gastric problems and for their anti-inflammatory properties. In this study, Maytenus aquifolium (Celastraceae) root bark ethanol extract was assessed for its ability to scavenge free radicals and reactive oxygen species. The results were expressed as percentage inhibition of the active species. The extract was efficient against studied reactive species: DPPH radical (obtained inhibition = 35.5 ± 1.3 %), ABTS.+ (IC50 = 0.0036 ± 0.0003 mg/mL), HOCl (IC50 = 0.002 ± 0.0001 mg/mL), O2 .- (obtained inhibition = 36.0 ± 2.1 %), and NO. (obtained inhibition = 18.3 ± 0.4 %). Uniterms Oxidant species Free radicals Maytenus aquifolium Oxidative damage.
Keywords: 1,1 diphenyl 2 picrylhydrazyl; 2,2' azinobis(3 ethylbenzothiazoline 6 sulfonic acid); alcohol; benzothiazoline derivative; free radical; hypochlorous acid; Maytenus aquifolium extract; nitric oxide; plant medicinal product; reactive oxygen metabolite; scavenger; antiinflammatory activity; antioxidant activity; bark; dyspepsia; Maytenus; medicinal plant; plant root; stomach ulcer; traditional medicine